What are the dimensions of thinking skills in Turkish literature: a content analysis study? - Yalçın Dilekli (Institute of Advanced Engineering and Science, 2019)
New world needs thinking generation. However, growing thinking generation is very difficult because there are many discrepancies in defining of thinking and thinking skills. Without defining thinking and its dimensions, it is nearly impossible to grow such generation. For having thinking generation, thinking and its dimensions should be described. In the past 20 years, there have been many different definitions with regard to thinking and thinking skills. But, three different approaches for defining thinking skills and needed basic cognitive operations were commonly accepted. Aim of this study whether these three approaches for defining thinking skills were accepted in Turkish literature or not. For this aim, 14 studies, selected from Turkish database, related to thinking skills were analyzed. According the content analysis results, Turkish literature follows these three movements for defining thinking skills except for belonging to specific areas.